2006
DOI: 10.1016/j.stam.2006.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bond defects on coiling of graphite

Abstract: The effect of annealing at 1400 1C in argon on the bond structure of graphite ball milled for 100 h at 400 rpm in polar (water) and in non-polar (n-dodecane) liquids was investigated primarily by near-edge X-ray absorption fine structure spectroscopy (NEXAFS) and transmission electron microscopy (TEM). Carbon K-edge NEXAFS allows the distortion of bonds in the hexagonal lattice to be investigated. It is shown that in-plane sp 2 bonds are strained and distorted after ball milling because sp 3 bonds are introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The Raman profiles exhibited in Figure 3d agree well with the XPS results where the intensity of the peak associated with defects at around 1350 cm −1 is stronger in DHPCs, giving rise to an increased I D /I G ratio, a widely used indicator to describe the relatively defective content in carbon materials. 42,43 Then, C K-edge NEXAFS was further used to investigate the structural feature (Figure 3e). Compared to NHPCs, DHPCs give a weak shoulder feature around 284.5 eV associated with edge characters (Figure 3e,f), indicative of the increased degree of graphitization in localized regions due to annealing at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman profiles exhibited in Figure 3d agree well with the XPS results where the intensity of the peak associated with defects at around 1350 cm −1 is stronger in DHPCs, giving rise to an increased I D /I G ratio, a widely used indicator to describe the relatively defective content in carbon materials. 42,43 Then, C K-edge NEXAFS was further used to investigate the structural feature (Figure 3e). Compared to NHPCs, DHPCs give a weak shoulder feature around 284.5 eV associated with edge characters (Figure 3e,f), indicative of the increased degree of graphitization in localized regions due to annealing at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Transmission Electron Microscopy examination (not shown) of ball-milled graphite reveals morphological changes similar to those we already reported in the literature. 24,27 During milling, the shear and impact forces continuously bend, fracture and displace the graphite sheets relative to each other and the ABAB. .…”
Section: Evolution Of Disorder During Millingmentioning
confidence: 99%
“…Elsewhere some of us demonstrated that during annealing in argon the system is driven to minimize the increased free energy by relief of the bond distortion and conjugation of the double in-plane bonds. 27,47 Besides, the stress accumulated during milling is minimised, at least in part, and by folding, corrugation and sometimes coiling of the graphene sheets. 24,27,47,48 To investigate the temperature stability of the magnetic susceptibility, sample G30 was heated to 1000 1C in argon (Ar) for 1 hour and after cooling down under inert gas conditions the susceptibility of the material was measured in the temperature interval 2-200 K (Fig.…”
Section: Modifications Of the Graphite Andmentioning
confidence: 99%
“…However, if X-ray diffraction gives accurate crystallographic information, spectroscopic methods give quantitative information on carbon content and the ratio of sp 2 /sp 3 bonds [1,2]. It is shown that in-plane sp 2 bonds are strained and distorted after ball milling because sp 3 bonds are introduced [3]. Much of what we know about the microstructures of these materials is obtained by use of picoscope [4].…”
Section: Introductionmentioning
confidence: 99%